PENGGUNAAN SERBUK BATU TABAS SEBAGAI PENGGANTI SEBAGIAN SEMEN DALAM PEMBUATAN BETON - Intara, I W.; Alit K. Salain, I M.; Anom Wiryasa, N. M. (JURNAL SPEKTRAN; Vol 1, No 1, Januari 2013DO - 10.24843/SPEKTRAN.2013.v01.i01.p01, 2013)
Research on the use of stone dust (SDT) as a partial replacement of Ordinary Portland Cement (OPC) has been carried out by using cylindrical concrete specimens with Ø = 150 mm and h = 300 mm. Specimens were made by using the ratio, in weight, of cementitious material : sand : crushed stone of 1.00 : 1.93 : 2.67. The water cementitious material ratio is of 0.52. The cementitious material is a mixture of OPC and SDT. The percentage of OPC replacement by SDT varied from 0%-25%. The distribution of grains of sand and crushed stone are designed according to SNI 03-2384-2000: gradation zone 2 for fine aggregate and gradation with a maximum diameter of 20 mm for coarse aggregate. The tests of compressive strength, elastic modulus, tensile strength and permeability on the cylindrical specimens were realized at 28 and 56 days. The result indicates that SDT shows a good pozzolanic reactivity in terms of compressive strength, elastic modulus, tensile strength and permeability. Therefore, it can be used as a component of Portland Cement Composite. The development of compressive strength, elastic modulus, tensile strength and permeability of concrete produced with a mixture of OPC and SDT depends on the amount of SDT used in the mixture and hydration time. The pozzolanic effect of SDT can only be seen at the age of 56 days. The optimal use of SDT as a partial replacement of OPC in concrete applications varied from 5%-10%.
Keywords: stone dust, compressive strength, elastic modulus, tensile strength, permeability